A method for recovering high-concentration VOCs tail gas from the breathing port of a storage tank
Through the combination of condensation, liquid adsorption and dry adsorption, sodium alginate/chitosan modified concave and convex rod clay/activated carbon adsorbent, the complex and low efficiency of the exhaust gas recovery process of high concentration VOCs at the tank breathing port is solved, and the problem of high concentration VOCs exhaust gas recovery process is achieved. Efficient and simple recycling process.
Patent Information
- Application Number
- CN202310242900.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-03-14
AI Technical Summary
The recycling of VOCs exhaust gas at the tank's breathing port has problems such as complex processes and low circulation efficiency.
Using a combination of condensation recovery, liquid adsorption and dry adsorption, sodium alginate/chitosan modified concave and convex rod clay/activated carbon as adsorption agent, the VOCs concentration is reduced and liquid adsorption is improved, and moisture is removed through dry adsorption. , prevent blockage.
It realizes efficient VOCs exhaust gas recovery with simple process, high recovery rate and high recycling rate, prevents adsorbent saturation and blockage, and improves adsorption effect and equipment reliability.
Smart Images

Figure CN116236874B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of tail gas recovery, and more specifically, relates to a method for recovering high-concentration VOCs tail gas at the breathing port of a storage tank. Background Art
[0002] VOC is a gas composed of a large number of volatile organic substances, so it is also called volatile organic pollutant gas; the World Health Organization (WHO) defines a large class of organic compounds with a boiling point range of 50-260℃, a saturated vapor pressure of more than 133.32 at room temperature, and existing in the air in the form of vapor at room temperature as volatile organic compounds (VOC). Its main components are hydrocarbons, halogenated hydrocarbons, nitrogen hydrocarbons, oxygen-containing hydrocarbons, sulfur hydrocarbons and low-boiling polycyclic aromatic hydrocarbons. Among the serious pollutions caused by VOC gases to the ecological environment, the pollution of the ozone layer is more serious, which also indirectly threatens human health.
[0003] In real life, VOC gases are inevitably emitted in the production activities of many chemical companies, resulting in high VOC gas emissions. Liquid medium raw materials, intermediate products, and products in the production activities of chemical companies are stored in tanks. In the organic liquid storage tank area during production activities, due to the state characteristics of large breathing and small breathing, more VOC gases with volatile characteristics will be produced. Therefore, the recovery of high-concentration VOCs tail gas at the breathing port of the storage tank has become an important part of environmental protection and emission reduction.
[0004] However, the current recovery of high-concentration VOCs tail gas from the breathing port of storage tanks has problems such as complex process and low circulation efficiency. Summary of the invention
[0005] The present invention provides a method for efficiently recovering high-concentration VOCs tail gas from the breathing port of a storage tank, which has the advantages of simple process, high recovery rate and high recycling rate.
[0006] The purpose of the present invention is to provide a method for recovering high-concentration VOCs tail gas from the breathing port of a storage tank.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A method for recovering high-concentration VOCs tail gas from a storage tank breathing port comprises the following steps:
[0009] (1) Condensation recovery: After cooling the tail gas containing VOCs at a temperature of 20 to 30°C, condense it at -10 to -2°C, and then heat the condensed gas phase in a heating device to 70 to 90°C before discharging it;
[0010] (2) Dry and wet adsorption: The gas phase discharged by heating is adsorbed in a liquid adsorption tank with water as the internal liquid at a temperature of 30-35°C, and then discharged after dry adsorption in a dry adsorption tank under the condition that the pressure at the gas phase input end is 50KPa greater than the pressure at the output end; the adsorbent used in the liquid adsorption tank is selected from sodium alginate / chitosan modified attapulgite clay / activated carbon;
[0011] (3) Desorption and recovery: The saturated adsorbent in the liquid adsorption tube and the dry adsorption tank is collected, and the saturated adsorbent is first subjected to ultrasonic desorption treatment with a solvent to recover the desorbed organic volatiles from the saturated adsorbent, and then the desorbed adsorbent is dried.
[0012] The above technical scheme first reduces the concentration of VOCs through condensation adsorption, which can prevent the adsorbent from being saturated too quickly under high concentration of VOCs during the dry and wet adsorption process and weaken the adsorption capacity of the adsorbent, and can effectively prevent VOCs from liquefying and blocking the pipe mouth by heating the gas phase after condensation; secondly, through liquid adsorption, the liquid slows down the air flow speed of the VOC gas phase. Compared with directly allowing the gas phase to pass through the adsorbent, it can better improve the adsorption efficiency of the adsorbent. At the same time, the gas phase can provide gas impact force after heating, impacting the adsorbent in the liquid adsorption tank to form a suspension, so that the adsorbent can better contact VOCs and improve the adsorption effect; finally, through dry adsorption, the moisture brought by the liquid adsorption is removed to prevent the exhaust port from being blocked by ice at the exhaust port due to the low ambient temperature when the moisture is discharged.
[0013] Furthermore, the step (3) further comprises 1-2% of the mass of the solvent as a surfactant; the surfactant is selected from any one of sodium dodecylbenzenesulfonate and hexadecyltrimethylammonium bromide.
[0014] Furthermore, in step (2), the drying adsorption tank comprises a three-layer structure, wherein the first layer is type B silica gel, the second layer is activated carbon, and the third layer is type B silica gel.
[0015] Furthermore, the preparation method of sodium alginate / chitosan modified attapulgite / activated carbon comprises the following steps:
[0016] (1) adding hydrochloric acid and deionized water to attapulgite clay, stirring at 80° C., cooling, filtering, washing with water until the filtrate is neutral, and drying to obtain acidified attapulgite clay; then taking the acidified attapulgite clay in a toluene solution, ultrasonically dispersing it, adding a silane coupling agent while stirring under N2 protection, continuing to reflux and stir, then adding a chitosan solution, ultrasonically dispersing it, and then stirring and reacting at 90° C., filtering, washing with an acetic acid solution and deionized water, and drying to obtain chitosan-modified attapulgite clay;
[0017] (2) heating sodium alginate and dissolving it in water, adding chitosan-modified attapulgite clay and stirring and mixing, then adding calcium chloride solution, continuing stirring, filtering, washing with water, and drying to obtain sodium alginate / attapulgite clay;
[0018] (3) calcining sodium alginate / attapulgite clay and activated carbon in a calcining furnace to obtain sodium alginate / chitosan modified attapulgite clay / activated carbon.
[0019] The above technical scheme makes the structure of the composite material denser through hydrogen bonds and electrostatic effects between sodium alginate, attapulgite and chitosan. After adding activated carbon to the composite, the wrinkles on the surface of the composite material can be further increased, the specific surface area can be increased, and the adsorption capacity can be improved; secondly, the -OH in the attapulgite clay and the -COOH or -OH in the sodium alginate are cross-linked with each other through electrostatic or hydrogen bonding, which increases the cross-linking density and gel strength of the composite material, thereby effectively inhibiting the swelling of the composite material and enhancing the hydrophobicity of the composite material, thereby preventing the activated carbon from swelling and absorbing water in liquid water and precipitating at the bottom of the adsorption tank, thereby reducing the contact between the adsorbent and the VOCs gas phase, and greatly reducing the adsorption effect.
[0020] Furthermore, the silane coupling agent is selected from any one of KH-550, KH560 and KH-570.
[0021] Furthermore, the solvent in step (3) is selected from high boiling point solvents, including 1,1,3-trimethylcyclohexenone.
[0022] The high-concentration VOCs tail gas recovery method of the present invention is mainly applied to the breathing port of a storage tank.
[0023] Beneficial effects:
[0024] (1) This technical solution first reduces the concentration of VOCs through condensation adsorption, which can prevent the adsorbent from being saturated too quickly under high concentrations of VOCs during the dry and wet adsorption process, thereby reducing the adsorption capacity of the adsorbent. In addition, by heating the gas phase after condensation, it can effectively prevent VOCs from liquefying and blocking the pipe opening. Secondly, liquid adsorption is used to slow down the air flow rate of the VOC gas phase. Compared with directly passing the gas phase through the adsorbent, the adsorption efficiency of the adsorbent can be better improved. At the same time, the gas phase can provide gas impact force after being heated to impact the adsorbent in the liquid adsorption tank, causing it to form a suspension, so that the adsorbent can better contact the VOCs and improve the adsorption effect. Finally, dry adsorption is used to remove the moisture brought by the liquid adsorption to prevent the exhaust port from being blocked by ice when the ambient temperature is too low when the moisture is discharged.
[0025] (2) The technical solution makes the composite material structure more compact through hydrogen bonding and electrostatic interaction between sodium alginate, attapulgite and chitosan. After adding activated carbon to the composite, the wrinkles on the surface of the composite material can be further increased, the specific surface area can be increased, and the adsorption capacity can be improved. Secondly, the -OH in the attapulgite clay and the -COOH or -OH in the sodium alginate are cross-linked with each other through electrostatic or hydrogen bonding, which increases the cross-linking density and gel strength of the composite material, thereby effectively inhibiting the swelling of the composite material and enhancing the hydrophobicity of the composite material, thereby preventing the activated carbon from swelling and absorbing water in liquid water and precipitating at the bottom of the adsorption tank, thereby reducing the contact between the adsorbent and the VOCs gas phase, and greatly reducing the adsorption effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a modular square frame structure used in the method for recovering high-concentration VOCs tail gas from the breathing port of a storage tank of the present invention. DETAILED DESCRIPTION
[0027] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0028] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0029] Example 1
[0030] Preparation of sodium alginate / chitosan modified attapulgite / activated carbon:
[0031] By weight, add 1 part of 30% hydrochloric acid and 130 parts of deionized water to 10 parts of attapulgite clay, stir at 80° C. for 1 hour, cool, filter, wash with water until the filtrate is neutral, and dry to obtain acidified attapulgite clay;
[0032] (1) taking the acidified attapulgite clay in 90 parts of toluene solution, ultrasonically dispersing it at an ultrasonic frequency of 300 kHz for 15 minutes, adding 2 parts of silane coupling agent while stirring under N2 protection, continuing reflux stirring, then adding 20 parts of 2% chitosan solution, ultrasonically dispersing it at an ultrasonic frequency of 200 kHz for 10 minutes, then stirring and reacting at 90° C. for 10 hours, filtering, washing with 0.3% acetic acid solution and deionized water for 3 times each, and drying to obtain chitosan-modified attapulgite clay; the silane coupling agent is selected from KH-550;
[0033] (2) adding 6 parts of sodium alginate to 100 parts of water and heating until dissolved, then adding the chitosan-modified attapulgite clay, stirring and mixing with a stirrer at 300 r / min for 30 min, then adding dropwise to 50 parts of 5% calcium chloride solution at 1 mL / min, continuing stirring for 30 min, filtering, washing with water, and drying to obtain sodium alginate / attapulgite clay;
[0034] (3) placing sodium alginate / attapulgite clay and activated carbon in a tube furnace under N2 atmosphere and heating the temperature to 340°C at a rate of 10°C / min for calcining for 2 h to obtain sodium alginate / chitosan modified attapulgite clay / activated carbon;
[0035] Recovery method of high-concentration VOCs tail gas from the breathing port of the storage tank:
[0036] (1) VOCs are discharged from the breathing port of the storage tank, then transported to the buffer tank through a pipeline, and then the VOCs tail gas in the buffer tank is transported to the cooling tank through a blower;
[0037] (2) Condensation recovery: After the VOCs-containing tail gas is initially cooled at 20°C, the cooled gas phase is transported to a condensation tank through a pipeline, condensed at -10°C, and then the condensed gas phase is transported to a temperature increaser through a pipeline, heated to 70°C, and then discharged;
[0038] (3) Dry and wet adsorption: The heated and discharged gas phase is transported through a pipeline to a liquid adsorption tank with water as the internal liquid at a temperature of 30°C for adsorption, and then the gas phase input pressure is controlled by a compressor to be 50 KPa higher than the output pressure, and then the gas phase is dry adsorbed in a dry adsorption tank before being discharged; the adsorbent used in the liquid adsorption tank is selected from sodium alginate / chitosan modified attapulgite clay / activated carbon; the dry adsorption tank includes a three-layer structure, the first layer is type B silica gel, the second layer is activated carbon, and the third layer is type B silica gel;
[0039] (4) Desorption and recovery: The saturated adsorbent in the liquid adsorption tank and the dry adsorption tank is collected and sent to the desorption and recovery system, and then the saturated adsorbent is desorbed by solvent ultrasound to recover the organic volatiles; the desorbed adsorbent is then dried to remove moisture and then recycled to recover VOCs; the solvent is selected from high boiling point solvents, including 1,1,3-trimethylcyclohexenone; the ultrasonic desorption process also includes a surfactant of 1% by mass of the solvent; the surfactant is selected from sodium dodecylbenzene sulfonate.
[0040] Example 2
[0041] Preparation of sodium alginate / chitosan modified attapulgite / activated carbon:
[0042] By weight, add 2 parts of 30% hydrochloric acid and 130 parts of deionized water to 10 parts of attapulgite clay, stir at 90° C. for 2 hours, cool, filter, wash with water until the filtrate is neutral, and dry to obtain acidified attapulgite clay;
[0043] (1) taking the acidified attapulgite clay in 90 parts of toluene solution, ultrasonically dispersing it at an ultrasonic frequency of 400 kHz for 20 minutes, adding 3 parts of silane coupling agent while stirring under N2 protection, continuing reflux stirring, then adding 30 parts of 2% chitosan solution, ultrasonically dispersing it at an ultrasonic frequency of 300 kHz for 15 minutes, then stirring and reacting at 95° C. for 12 hours, filtering, washing with 0.3% acetic acid solution and deionized water for 3 times each, and drying to obtain chitosan-modified attapulgite clay; the silane coupling agent is selected from KH560;
[0044] (2) adding 6 parts of sodium alginate to 100 parts of water and heating until dissolved, then adding the chitosan-modified attapulgite clay, stirring and mixing with a stirrer at 400 r / min for 35 min, then adding dropwise to 55 parts of 5% calcium chloride solution at 2 mL / min, continuing stirring for 40 min, filtering, washing with water, and drying to obtain sodium alginate / attapulgite clay;
[0045] (3) placing sodium alginate / attapulgite clay and activated carbon in a tubular furnace under N2 atmosphere and heating the temperature to 370°C at a rate of 15°C / min for calcining for 3 h to obtain sodium alginate / chitosan modified attapulgite clay / activated carbon;
[0046] Recovery method of high-concentration VOCs tail gas from the breathing port of the storage tank:
[0047] (1) High-concentration VOCs are discharged from the breathing port of the storage tank, then transported to the buffer tank through a pipeline, and then the VOCs tail gas in the buffer tank is transported to the cooling tank through a blower;
[0048] (2) Condensation recovery: After the VOCs-containing tail gas is initially cooled at a temperature of 25°C, the cooled gas phase is transported to a condensation tank through a pipeline, condensed at -4°C, and then the condensed gas phase is transported to a temperature increaser through a pipeline, heated to 80°C, and then discharged;
[0049] (3) Dry and wet adsorption: The heated and discharged gas phase is transported through a pipeline to a liquid adsorption tank with water as the internal liquid at a temperature of 32°C for adsorption, and then the gas phase input pressure is controlled by a compressor to be 50Kpa higher than the output pressure, and then the gas phase is dry adsorbed in a dry adsorption tank before being discharged; the adsorbent used in the liquid adsorption tank is selected from sodium alginate / chitosan modified attapulgite clay / activated carbon; the dry adsorption tank includes a three-layer structure, the first layer is B-type silica gel, the second layer is activated carbon, and the third layer is B-type silica gel;
[0050] (4) Desorption and recovery: The saturated adsorbent in the liquid adsorption tank and the dry adsorption tank is collected and sent to the desorption and recovery system, and then the saturated adsorbent is desorbed by solvent ultrasound to recover the organic volatiles; the desorbed adsorbent is then dried to remove moisture and then recycled to recover VOCs; the solvent is selected from high boiling point solvents, including 1,1,3-trimethylcyclohexenone; the ultrasonic desorption process also includes a surfactant of 1.5% by mass of the solvent; the surfactant is selected from hexadecyltrimethylammonium bromide.
[0051] Example 3
[0052] Preparation of sodium alginate / chitosan modified attapulgite / activated carbon:
[0053] By weight, 0.5 parts of 30% hydrochloric acid and 130 parts of deionized water were added to 10 parts of attapulgite clay, stirred at 70° C. for 30 minutes, cooled, filtered, washed with water until the filtrate was neutral, and dried to obtain acidified attapulgite clay;
[0054] (1) taking the acidified attapulgite clay in 90 parts of toluene solution, ultrasonically dispersing it at an ultrasonic frequency of 200 kHz for 10 minutes, adding 1 part of silane coupling agent while stirring under N2 protection, continuing reflux stirring, then adding 15 parts of 2% chitosan solution, ultrasonically dispersing it at an ultrasonic frequency of 100 kHz for 5 minutes, then stirring and reacting at 85°C for 8 hours, filtering, washing with 0.3% acetic acid solution and deionized water for 3 times each, and drying to obtain chitosan-modified attapulgite clay; the silane coupling agent is selected from KH-570;
[0055] (2) adding 6 parts of sodium alginate to 100 parts of water and heating until dissolved, then adding the chitosan-modified attapulgite clay, stirring and mixing with a stirrer at a speed of 200 r / min for 20 minutes, and then adding dropwise to 45 parts of 5% calcium chloride solution at a rate of 0.5 mL / min, continuing to stir for 20 minutes, filtering, washing with water, and drying to obtain sodium alginate / attapulgite clay;
[0056] (3) placing sodium alginate / attapulgite clay and activated carbon in a tubular furnace under N2 atmosphere and heating the temperature to 300°C at a rate of 5°C / min for calcining for 1 h to obtain sodium alginate / chitosan modified attapulgite clay / activated carbon;
[0057] Recovery method of high-concentration VOCs tail gas from the breathing port of the storage tank:
[0058] (1) High-concentration VOCs are discharged from the breathing port of the storage tank, then transported to the buffer tank through a pipeline, and then the VOCs tail gas in the buffer tank is transported to the cooling tank through a blower;
[0059] (2) Condensation recovery: After the VOCs-containing tail gas is initially cooled at 30°C, the cooled gas phase is transported to a condensation tank through a pipeline, condensed at -2°C, and then the condensed gas phase is transported to a temperature increaser through a pipeline, heated to 90°C, and then discharged;
[0060] (3) Dry and wet adsorption: The heated and discharged gas phase is transported through a pipeline to a liquid adsorption tank with water as the internal liquid at a temperature of 35°C for adsorption, and then the gas phase input pressure is controlled by a compressor to be 50Kpa higher than the output pressure, and then the gas phase is dry adsorbed in a dry adsorption tank before being discharged; the adsorbent used in the liquid adsorption tank is selected from sodium alginate / chitosan modified attapulgite clay / activated carbon; the dry adsorption tank includes a three-layer structure, the first layer is type B silica gel, the second layer is activated carbon, and the third layer is type B silica gel;
[0061] (4) Desorption and recovery: The saturated adsorbent in the liquid adsorption tank and the dry adsorption tank is collected and sent to the desorption and recovery system, and then the saturated adsorbent is desorbed by solvent ultrasound to recover the organic volatiles; the desorbed adsorbent is then dried to remove moisture and then recycled to recover VOCs; the solvent is selected from high boiling point solvents, including 1,1,3-trimethylcyclohexenone; the ultrasonic desorption process also includes a surfactant of 2% by mass of the solvent; the surfactant is selected from sodium dodecylbenzene sulfonate.
[0062] Comparative Example 1
[0063] The difference between this comparative example and Example 1 is that activated carbon is used instead of the sodium alginate / chitosan modified attapulgite clay / activated carbon composite material as the adsorbent.
[0064] Comparative Example 2
[0065] The difference between this comparative example and Example 1 is that no liquid adsorption is performed, and the gas phase is condensed and directly transported to the dry adsorption tank through a pipeline.
[0066] The performance tests were performed on the products obtained in Examples 1-3 and Comparative Examples 1-2. The specific test methods and test results are as follows:
[0067] The recovery rate of VOCs tail gas at the breathing port of the storage tank is determined according to the standard of HJ732-2014;
[0068] The specific test results are shown in Table 1;
[0069] Table 1: VOCs tail gas recovery test results
[0070] Recovery rate / % Example 1 99.4% Example 2 99.0% Example 3 98.7% Comparative Example 1 85.4% Comparative Example 2 81.1%
[0071] It can be seen from the test results in Table 1 that the present invention has a higher recovery rate for high-concentration VOCs tail gas from the breathing port of the storage tank.
[0072] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for recovering high-concentration VOCs tail gas from the breathing port of a storage tank, characterized in that: The following steps are involved: (1) Condensation recovery: Cool the exhaust gas containing VOCs at a temperature of 20-30°C, condense it at -10--2°C, and then heat the condensed gas phase in a heating device to 70-90°C before discharging it; (2) Dry and wet adsorption: The gas phase discharged by heating is adsorbed in a liquid adsorption tank with water as the internal liquid at a temperature of 30-35°C, and then discharged after dry adsorption in a dry adsorption tank under the condition that the pressure at the gas phase input end is 50 kPa higher than the pressure at the output end; the adsorbent used in the liquid adsorption tank is sodium alginate / chitosan modified attapulgite clay / activated carbon; (3) Desorption and recovery: Collect the saturated adsorbent in the liquid adsorption tube and the dry adsorption tank, first subject the saturated adsorbent to ultrasonic desorption treatment with a solvent to recover the desorbed organic volatiles from the saturated adsorbent, and then dry the desorbed adsorbent; The step (3) further comprises a surfactant in an amount of 1-2% by mass of the solvent; the surfactant is selected from any one of sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium bromide; In the step (2), the drying adsorption tank comprises a three-layer structure, wherein the first layer is type B silica gel, the second layer is activated carbon, and the third layer is type B silica gel; The preparation method of sodium alginate / chitosan modified attapulgite / activated carbon comprises the following steps: (a) adding hydrochloric acid and deionized water to attapulgite clay, stirring at 80° C., cooling, filtering, washing with water until the filtrate is neutral, and drying to obtain acidified attapulgite clay; then taking the acidified attapulgite clay in a toluene solution, ultrasonically dispersing, adding a silane coupling agent while stirring under N2 protection, continuing to reflux and stir, then adding a chitosan solution, ultrasonically dispersing, and then stirring and reacting at 90° C., filtering, washing with an acetic acid solution and deionized water, and drying to obtain chitosan-modified attapulgite clay; (b) heating sodium alginate to dissolve in water, adding chitosan-modified attapulgite clay and stirring to mix, then adding calcium chloride solution, continuing to stir, filtering, washing with water, and drying to obtain sodium alginate / attapulgite clay; (c) calcining sodium alginate / attapulgite clay and activated carbon in a calcining furnace to obtain sodium alginate / chitosan modified attapulgite clay / activated carbon, the calcination temperature being between 300°C and 370°C; In the step (a), the silane coupling agent is selected from any one of KH-550, KH560, and KH-570; The solvent in step (c) is 1,1,3-trimethylcyclohexenone; The method for recovering high-concentration VOCs tail gas is mainly applied to the breathing port of the storage tank.
